Culture of attenuated Salmonella Typhimurium VNP20009 in animal-product-free media does not alter schwannoma growth control - Sherif G. Ahmed; Giulia Oliva; Manlin Shao; John J. Mekalanos; Gary J. Brenner (Taylor & Francis Group, 2023)
Schwannomas are slow-growing benign peripheral nerve sheath tumors derived from Schwann-lineage cells that develop in association with NF2-related schwannomatosis (NF2) and schwannomatosis (NF3), as well as spontaneously. Individuals affected with NF2 and NF3 have multiple schwannomas with tumors arising throughout life. Surgical resection, the standard management, is limited in scope and efficacy and is itself associated with significant morbidity. We have previously shown that direct intratumoral injection of attenuated Salmonella Typhimurium (S. Typhimurium), strain VNP20009, showed a potent anti-tumor effect in preclinical NF-2 schwannoma models. The United States Federal Drug Administration (FDA) requires that bacterial products utilized in clinical trials be produced without exposure to animal-derived-products. In this context, we developed, characterized, and tested the antitumor efficacy of an attenuated S. Typhimurium serially passaged in animal-product-free media, naming it VNP20009-AF for "VNP20009-animal-product-free." Our in vitro data did not indicate any significant changes in the viability, motility, or morphology of VNP20009-AF, compared to its parental strain. In vivo efficacy data demonstrated that VNP20009-AF and VNP20009 controlled tumor growth to the same degree in both human NF2-schwannoma xenograft and murine-NF2 schwannoma allograft models. Together, these data support the use of VNP20009-AF for the translation of bacterial schwannoma therapy into clinical trials.